The Efficiency of Attentional Networks in Early and Late Bilinguals: The Role of Age of Acquisition - Tao, Lily; Marzecová, Anna; Taft, Marcus; Asanowicz, Dariusz; Wodniecka, Zofia (Frontiers in Psychology, 2011)
Previous studies have demonstrated a bilingual advantage in the efficiency of executive attention. A question remains, however, about the impact of the age of L2 acquisition and relative balance of the two languages on the enhancement of executive functions in bilinguals, and whether this is modulated by the similarity of the bilingual’s two languages. The present study explores these issues by comparing the efficiency of attentional networks amongst three groups of young adults living in Australia: English monolinguals and early and late Chinese-English bilinguals. We also address the impact of bilingualism on hemispheric lateralization of cognitive functions, which is of interest since a recent study on early bilinguals revealed reduced hemispheric asymmetry in attentional functioning. In the present study, participants performed a modified version of the lateralized attention network test (LANT). Both early and late bilinguals were found to have more efficient executive network than monolinguals. The late bilinguals, who were also reported to be more balanced in the proficiency and usage of their two languages, showed the greatest advantage in conflict resolution, whereas early bilinguals seemed to show enhanced monitoring processes. These group differences were observed when controlling for nonverbal intelligence and socioeconomic status. Such results suggest that specific factors of language experience may differentially influence the mechanisms of cognitive control. Since the bilinguals had distinct language sets, it seems that the influence of bilingualism on executive functions is present regardless of the similarity between the two languages. As for hemispheric lateralization, although the results were not clear-cut, they suggest the reduced lateralization in early bilinguals.